New species of the Afrotropical spider genus Cheiramiona Lotz & Dippenaar-Schoeman (Araneae: Eutichuridae) - Lotz, L.n. (Zootaxa, 2015)
Twenty-three new species of the Afrotropical sac spider genus Cheiramiona Lotz & Dippenaar-Schoeman, 1999 are described: C. baviaan sp. nov. (♀, South Africa), C. boschrandensis sp. nov. (♀, South Africa), C. debeeri sp. nov. (♂, South Africa), C. haddadi sp. nov. (♂, South Africa), C. hlathikulu sp. nov. (♂, South Africa), C. hogsbackensis sp. nov. (♀, ♂, South Africa), C. ibayaensis sp. nov. (♂, Tanzania), C. jakobsbaaiensis sp. nov. (♂, South Africa), C. kirkspriggsi sp. nov. (♀, ♂, South Africa), C. kivuensis sp. nov. (♀, ♂, Democratic Republic of Congo & Rwanda), C. lamorali sp. nov. (♂, Namibia), C. lindae sp. nov. (♂, South Africa), C. malawiensis sp. nov. (♀, ♂, Malawi), C. mkhambathi sp. nov. (♀, ♂, South Africa), C. mohalensis sp. nov. (♀, Lesotho), C. musosaensis sp. nov. (♀, Democratic Republic of Congo), C. nyungwensis sp. nov. (♂, Rwanda), C. plaatbosensis sp. nov. (♀, ♂, South Africa), C. qachasneki sp. nov. (♂, South Africa), C. robinae sp. nov. (♂, South Africa), C. saniensis sp. nov. (♀, ♂, South Africa), C. tembensis sp. nov. (♂, South Africa) and C. upperbyensis sp. nov. (♀, South Africa). The females of C. lajuma Lotz, 2002 and C. mlawula Lotz, 2002 are described for the first time.